Intracellular metabolism of (-)- and (+)-cis-5-fluoro-1-[2-(hydroxymethyl)-1,3-oxathiolan-5-yl]cytosine in HepG2 derivative 2.2.15 (subclone P5A) cells. - Paff, M T (1994)
The (-) and (+) enantiomers of the nucleoside analog cis-5-fluoro-1-[2-(hydroxymethyl)-1,3-oxathiolan-5-yl]cytosine (2',3'-dideoxy-5-fluoro-3'-thiacytidine; FTC) have been shown to inhibit hepatitis B virus replication in vitro in HepG2 derivative 2.2.15 (subclone P5A) cells. (-)-FTC and (+)-FTC were anabolized to 5'-monophosphate, 5'-diphosphate, and 5'-triphosphate in this cell line. (-)-FTC was more efficiently phosphorylated to the 5'-triphosphate than (+)-FTC, and levels of 3.6 and 0.2 pmol/10(6) cells, respectively, were detected after incubation with 1 microM compound for 24 h. A time course study showed that nucleotides were formed rapidly in a dose-dependent manner and reached a steady-state intracellular concentration by 3 to 6 h. The intracellular half-life of (-)-FTC 5'-triphosphate was 2.4 h. Both (-)- and (+)-FTC were converted to diphosphocholine derivatives, analogous to CDP-choline, but only (+)-FTC was converted to the diphosphoethanolamine derivative, analogous to CDP-ethanolamine. (-)-FTC was not detectably deaminated at either the nucleoside or nucleotide level. (+)-FTC was partially deaminated by these cells. The transport of (-)-and (+)-FTC was examined in HepG2 cells. (+)-FTC enters these cells by way of the nitrobenzylthioinosine-susceptible, equilibrative nucleoside transporter. In contrast, the influx of (-)-FTC was only partially susceptible to inhibitors of nucleoside transport, indicating that (-)-FTC may have multiple transport mechanisms. These metabolic results are consistent with the conclusion that (-)-FTC 5'-triphosphate mediates the anti-hepatitis B virus activity of (-)-FTC.